2005
DOI: 10.1007/s10754-005-6599-x
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Welfare Implications of Parallel Imports in the Pharmaceutical Industry

Abstract: In this paper we investigate the implications of permitting parallel imports of pharmaceuticals produced by a monopoly, from one country to another. We use a model where countries differ in the patients' level of co-payment for buying pharmaceuticals, and patients differ in the utility obtained from the consumption of pharmaceuticals. We show that the effects of parallel imports on total welfare are as follows: On the one hand, when countries differ in their health system only, parallel imports decrease total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 9 publications
1
54
1
Order By: Relevance
“…Jelovac and Bordoy (2005). For the purpose of this paper, it is sufficient to assume that p s is low enough for parallel trade to take place.…”
Section: P Imentioning
confidence: 99%
See 1 more Smart Citation
“…Jelovac and Bordoy (2005). For the purpose of this paper, it is sufficient to assume that p s is low enough for parallel trade to take place.…”
Section: P Imentioning
confidence: 99%
“…The theoretical literature regarding parallel trade includes Pecorino (2002), Ganslandt and Maskus (2004), Maskus and Chen (2004), Jelovac and Bordoy (2005) and Chen and Maskus (2005), which show, among other things, that parallel imports should create price competition and cause prices to fall in the high-price country. This is supported empirically by Ganslandt and Maskus (2004) who found that competition from parallel imports reduced prices on locally sourced drugs by 12-19%.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a theoretical paper by Köksal (2009) showing that reference pricing should increase price competition from parallel imports. The theoretical literature regarding parallel trade also includes Pecorino (2002), Ganslandt and Maskus (2004), Maskus and Chen (2004), Jelovac and Bordoy (2005), and Chen and Maskus (2005), which show, among other things, that parallel imports should create price competition and cause prices to fall in the destination country. The empirical literature about the effects of competition from parallel imports is limited to Ganslandt and Maskus (2004), Kanavos and Costa-Font (2005), Kanavos and Vandoros (2010), Kyle (2011) and Duso et al (2014), none of them addressed reference pricing or substitution reforms in general.…”
Section: Introductionmentioning
confidence: 99%
“…This is also controversial, as preventing parallel trade by means of private contracts could be considered an anticompetitive behavior that prevails under competition law (Gallini and Hollis, 1999). 4 Parallel trade does not imply necessarily price convergence if consumers do not believe that the original drug and the parallel imported drug have the same value (Jelovac and Bordoy, 2005). Empirical studies in the EU include Ganslandt and Maskus (2004), Kanavos and Costa-Font (2005) and Kyle (2007).…”
Section: Accepted Manuscript 2 International Exhaustion and Parallel mentioning
confidence: 99%
“…The interference of national governments in private markets by way of regulation of drug prices is, in particular, a factor causing price differences at the international level (Pecorino, 2002;Jelovac and Bordoy, 2005;Saggi, 2013).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%